Diversity of scarab beetles (Coleoptera) in the main habitat conditions of Montebello, Chiapas, Mexico - Delgado, Juan Manuel; Castro-Ramírez, Adriana Elena; Morón Ríos, Miguel Ángel; Ruiz-Montoya, Lorena (Instituto de Ecología, A.C., 2012)
Lagunas de Montebello National Park in Chiapas, is considered an important area for biodiversity conservation in Mexico, so we was studied the fauna of Scarabaeoidea in the main habitat conditions: montane rain (MRF), pine-oak-sweetgum (POSF) and pine (PF), during February to August 2010. The beetles was obtained using 27 traps baited with ferments of banana (Musa paradisiaca), nine pitfall traps baited with human feces, 27 pitfall traps baited with squid meat, three white fluorescent light traps, three black light traps and the direct capture of individuals. We obtained a total of 67 speciesbelonging to three families and 31 genera. The type of vegetation richer was MRF with 46 species, followed by POSF and PF with 41 and 35 species respectively. However, the exponential of the Shannon-Wiener index obtained its highest value in the PF recording 10.91 species. Clench’s equation and the linear dependence model estimated a capture effort of 68% and 94% respectively. The estimation of beta diversity was calculated using Jaccard’s Coefficient and Complementarity. We was recorded the biggest similarity between the faunas of POSF and MRF (0.49), while the highest dissimilarity was presented at the MRF-PF ratio (0.62). The influence of precipitation was determined with Spearman correlations, being significant with the species richness of the MRF (Rho = 0.73; p = 0.007), POSF (Rho = 0.67; p = 0.018) y PF (Rho = 0.68; p = 0.015), while the abundance was significantly correlated with precipitation in the MRF (Rho = 0.61, p = 0.035). It is important conservation areas such as the Lagunas de Montebello National Park, which has a different forest types and an increase in the intensity of human activities in recent years, even in areas subject to preservation possibly affecting species with habitat specificity.